Revenues and welfare in auctions with information release - Nikolaus Schweizer; Nora Szech (Karlsruher Institut für Technologie (KIT), Institut für Volkswirtschaftslehre (ECON), 2015)
Auctions are the allocation-mechanisms of choice whenever goods and information in markets are scarce. Therefore, understanding how information affects welfare and revenues in these markets is of fundamental interest. We introduce new statistical concepts, k- and k-m-dispersion, for understanding the impact of information release. With these tools, we study the comparative statics of welfare versus revenues for auctions with one or more objects and varying numbers of bidders. Depending on which parts of a distribution of valuations are most affected by information release, welfare may react more strongly than revenues, or vice versa.
urn:nbn:de:swb:90-471034
Keywords: D44; D82; 330; Auctions; Information Release; Information Partitions; Order Statistics; Stochastic Orders; Dispersion; Dispersive Order; Excess Wealth Order